Chinese Stock Returns and the Role of News-Based Uncertainty. Issue 13 (21st October 2019) - Su, Zhi; Lu, Man; Yin, Libo
ABSTRACT: Academic research relies extensively on fundamentals to forecast stock returns, with relatively little attention paid to the news channel. To fill this gap, we use the NVIX as a proxy for news-based uncertainty, to investigate its predictive power for Chinese stock returns wavelet analysis and prediction framework. We find that the long-term NVIX statistically and economically predicts Chinese stock returns in an in-sample and out-of-sample analysis, while the short-term NVIX almost has no predictability. In addition, we confirm the links between the long-term NVIX and the US and Chinese real economy, which might be why the long-term NVIX has good predictability for Chinese stock returns.